Consistency and Inconsistency of Young Women's Reporting of Intimate Partner Violence in a Population-Based Study. (March 2021) - Rowlands, Ingrid J.; Holder, Carl; Forder, Peta M.; Hegarty, Kelsey; Dobson, Annette J.; Loxton, Deborah
We examined reporting of lifetime intimate partner violence (IPV) among 7, 917 young women who completed two surveys, 12 months apart. At the first survey, 32% reported a history of IPV with a current or former partner. Of these, one third of women did not report IPV 12 months later (inconsistently reported IPV). Compared with women who consistently reported a history of IPV, women who inconsistently reported a history of IPV were less likely to report suicidal ideation, self-harm, illicit drug use, and smoking at the 12-month follow-up. A deeper understanding of what influences young women's reporting of IPV is needed.